Polarisation Mode Beating and Self-Sustained Pulsation in Optically Pumped Birefringent Vertical Cavity Surface Emitting Lasers - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2004)
This study developed a VCSEL model for this device and incorporated cavity birefringence based on a described method. The laser chirp and Kerr self-phase modulation have been included in the model as well, though it can be shown that cavity birefringence has the dominant impact on the polarization properties of the VCSELs. Simulation shows that birefringence manifest when the output power is measured with a polarizer that bisects the crystallographic axes. Polarization mode beating is observed with a beating frequency determined largely by the cavity's birefringence. These simulations are in good agreement with experimental results.